2012
DOI: 10.5194/bg-9-309-2012
|View full text |Cite
|
Sign up to set email alerts
|

Pteropods from the Caribbean Sea: variations in calcification as an indicator of past ocean carbonate saturation

Abstract: Abstract. The aragonite shell-bearing thecosome pteropods are an important component of the oceanic plankton. However, with increasing pCO 2 and the associated reduction in oceanic pH (ocean acidification), thecosome pteropods are thought to be particularly vulnerable to shell dissolution. The distribution and preservation of pteropods over the last 250 000 years have been investigated in marine sediment cores from the Caribbean Sea close to the island of Montserrat. Using the Limacina Dissolution Index (LDX),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Because of their mineralogy, pteropod shells are often diagenetically altered, limiting their use in palaeoceanographic studies (Manno et al, 2017). Pteropod preservation in the fossil record is interpreted to be controlled by Ω arag in the surface ocean (Wall-Palmer et al, 2012) and at the sediment-water interface (Berger, 1978;Berner et al, 1976;Gerhardt et al, 2000;Gerhardt & Henrich, 2001). Based on the results of this study, we postulate that the organic matter content of the water column and sediments at the seafloor may have a large influence on the preservation potential of pteropod shells in the fossil record (Almogi-Labin et al, 1986).…”
Section: Fossil Recordmentioning
confidence: 99%
“…Because of their mineralogy, pteropod shells are often diagenetically altered, limiting their use in palaeoceanographic studies (Manno et al, 2017). Pteropod preservation in the fossil record is interpreted to be controlled by Ω arag in the surface ocean (Wall-Palmer et al, 2012) and at the sediment-water interface (Berger, 1978;Berner et al, 1976;Gerhardt et al, 2000;Gerhardt & Henrich, 2001). Based on the results of this study, we postulate that the organic matter content of the water column and sediments at the seafloor may have a large influence on the preservation potential of pteropod shells in the fossil record (Almogi-Labin et al, 1986).…”
Section: Fossil Recordmentioning
confidence: 99%
“…The Atlantic‐type carbonate preservation signal results mainly from changes in the formation and export of NADW (Broecker & Clark, ; Hodell et al, ; Howard & Prell, ). This is supported by contrasting carbonate preservation signals in the deep and shallow Atlantic: widespread carbonate dissolution occurred in the last glacial in the deep Atlantic, which was occupied by predominantly southern sourced water masses (Bickert & Wefer, ; Gottschalk et al, ; Hodell et al, ; Howard & Prell, ; Yu et al, ), while enhanced carbonate preservation was found at shallower depths that were occupied by Glacial North Atlantic Intermediate Water (GNAIW; Haddad & Droxler, ; Henrich et al, ; Wall‐Palmer et al, ). The coevolution of changes in carbonate dissolution with AMOC variability in the glacial Atlantic underlines its primary association with water mass dynamics (and the evolving geochemical signatures of deep water end‐members) rather than whole‐ocean adjustments to an imbalance in the DIC and alkalinity inventories.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by contrasting carbonate preservation signals in the deep and shallow Atlantic: widespread carbonate dissolution occurred in the last glacial in the deep Atlantic, which was occupied by predominantly southern sourced water masses (Bickert & Wefer, 1996;Gottschalk et al, 2015;Hodell et al, 2001;Howard & Prell, 1994;Yu et al, 2008), while enhanced carbonate preservation ]) in bottom waters in the Southeast Atlantic (Key et al, 2004), thin line tracks the 4-(stippled) and 2-km isobaths (solid); the position of major fronts are shown in dark gray (Polar Front), in gray (Sub-Antarctic Front), and in light gray (Sub-Tropical Front;Orsi et al, 1995;Sokolov & Rintoul, 2009); deep ocean currents are shown after Tucholke and Embley (1984) and Stramma and England (1999 (Key et al, 2004). Circles indicate the was found at shallower depths that were occupied by Glacial North Atlantic Intermediate Water (GNAIW; Haddad & Droxler, 1996;Henrich et al, 2003;Wall-Palmer et al, 2012). The coevolution of changes in carbonate dissolution with AMOC variability in the glacial Atlantic underlines its primary association with water mass dynamics (and the evolving geochemical signatures of deep water end-members) rather than whole-ocean adjustments to an imbalance in the DIC and alkalinity inventories.…”
Section: Introductionmentioning
confidence: 99%
“…The calibrations established here will be of use to the ocean acidification and paleo-oceanographic community, as the studied species, H . inflatus , occurs in high abundance in sediments worldwide 20 , for instance, in the Central and South Atlantic 21 or the Caribbean Sea 22 .…”
Section: Introductionmentioning
confidence: 99%